Responsive or Responsible? On the policy implementation of popular initiative under challenges of international law - Bernhard, Laurent (Politics of the Low Countries, 2025)
The scant literature on policy implementation in direct democracy has found that non-compliance with accepted initiatives is rather widespread. Political scientists have mainly explained this finding by focusing on the preferences of those actors in charge of implementation, thereby neglecting supranational restrictions. This article advances the literature by focusing on the challenge posed by international law. It is argued that the implementation of initiatives that conflict with international law poses a dilemma between responsiveness (i.e., respecting the people’s will) and responsibility (i.e., complying with a country’s external obligations). A case study of the Swiss deportation initiative shows that legislators relied as much as possible on responsiveness by enacting a decisive tightening of penal legislation according to the basic demands of the accepted proposition and as little as necessary on responsibility, given that MPs refrained from implementing those provisions that conflicted with mandatory international law.